2004
DOI: 10.1007/s10396-004-0015-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of a new method that segments the region of interest into multiple layers for RF amplitude histogram analysis in the cirrhotic liver

Abstract: These results suggest that the new method can be used to diagnose the cirrhotic liver objectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…On the other hand, a correlation between histological changes and acoustic characteristics has been reported in quantitative studies using statistical analysis of RF signal amplitude (a more objective method of evaluation) [11][12][13][14][15][16][17], but this correlation has not yet been made use of in clinical practice. One reason is the difficulty of linking the results of statistical analysis to findings from B-mode images.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, a correlation between histological changes and acoustic characteristics has been reported in quantitative studies using statistical analysis of RF signal amplitude (a more objective method of evaluation) [11][12][13][14][15][16][17], but this correlation has not yet been made use of in clinical practice. One reason is the difficulty of linking the results of statistical analysis to findings from B-mode images.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, tissue characterization of the liver has been used as a simple, objective alternative to liver biopsy; this involves statistical analysis of the speckle signal from the liver parenchyma [11][12][13][14][15][16][17]. The results from these studies have revealed there is a correlation between histological changes and acoustic characteristics, although acoustic characteristics have not yet been applied in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Our group also quantified liver fibrosis by analyzing the echo amplitude envelope [18][19][20][21][22][23][24]. Envelope statistics are often used for tissue characterization using ultrasound [13,15]. It is possible to roughly estimate the progress of fibrosis by previous research results including our research.…”
Section: Introductionmentioning
confidence: 99%
“…In ultrasound tissue characterization based on the characteristics of the echo signal such as power spectrum, texture parameters, local attenuation, and statistical characteristics, it is assumed that changes in tissue properties such as attenuation and elasticity are uniform in the liver, and a single evaluation index is therefore used in many methods [10][11][12][13][14][15][16][17]. Our group also quantified liver fibrosis by analyzing the echo amplitude envelope [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There are several approaches found in the literature. Some authors have evaluated the RF signal [1,2], while others have proposed some visual scores [3,4], but most authors have employed a texture analysis system to discriminate between various fibrosis stages [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%